PLGA Microspheres Incorporated Gelatin Scaffold: Microspheres Modulate Scaffold Properties - Indranil Banerjee; Debasish Mishra; Tapas K. Maiti (International Journal of Biomaterials)
Freeze drying is one of the popular methods of fabrication for poly(lactide-co-glycolide) (PLGA) microspheres incorporated polymer scaffolds. However, the consequence of microspheres incorporation on physical and biological properties of scaffold has not been studied yet. In this study, attempt has been made to characterize the effect of PLGA microsphere incorporation on the physical properties of freeze-dried gelatin scaffold and its influence on cytocompatibility. Scaffolds loaded with varying amount of PLGA microspheres (10%, 1%, 0.1% w/w) were subjected to microarchitecture analysis, swelling, porosity, mechanical properties, biodegradation, cell adhesion, and cell proliferation studies. Results revealed that an increase in percentage loading of microspheres reduced the pore size and uniformity of the pore structure. Moreover, loading of PLGA microspheres up to 1% w/w significantly increased porosity, swelling, and mechanical properties of the scaffold but variations were not proportional for 10% w/w loading. Results also showed that PLGA microspheres have no significant effect on cell adhesion but influenced the growth kinetics.